Analisis Pengaruh Inflasi dan Harga Sukuk Ritel SR-008 terhadap Permintaan Sukuk Ritel SR-008 - Ahmad Fauzi (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2019)
This study aims to analyze the effect of the inflation rate and price of Sukuk Negara Ritel SR-008 on the level of demand of Sukuk Negara Ritel SR-008. This study uses data of market price and monthly sales volume of SR-008 during the period March 2015 to December 2017 with multiple linear regression analysis tool. The result shows that the variable of the inflation rate and price of SR-008 had an insignificantly negative effect on the level of demand for SR-008.